In situ structural analysis of calcium aluminosilicate glasses under high pressure. (14th June 2016) - Muniz, R F; de Ligny, D; Martinet, C; Sandrini, M; Medina, A N; Rohling, J H; Baesso, M L; Lima, S M; Andrade, L H C; Guyot, Y
Abstract: In situ micro-Raman spectroscopy was used to investigate the structural evolution of OH − -free calcium aluminosilicate glasses, under high pressure and at room temperature. Evaluation was made of the role of the SiO2 concentration in percalcic join systems, for Al/(Al + Si) in the approximate range from 0.9 to 0.2. Under high pressure, the intensity of the main band related to the bending mode of bridging oxygen ( ν B [T-O-T], where T = Si or Al) decreased gradually, suggesting that the bonds were severely altered or even destroyed. In Si-rich glasses, compression induced a transformation of Q n species to Q n −1 . In the case of Al-rich glass, the Al in the smallest Q n units evolved from tetrahedral to higher-coordinated Al ( [5] Al and [6] Al). Permanent structural changes were observed in samples recovered from the highest pressure of around 15 GPa and, particularly for Si-rich samples, the recovered structure showed an increase of three-membered rings in the Si/Al tetrahedral network.